Breaking the Bank? : A Probabilistic Assessment of Euro Area Bank Profitability - Elekdag, Selim (IMF Working Papers; Working Paper ;, 2019)
This paper explores the determinants of profitability across large euro area banks using a novel approach based on conditional profitability distributions. Real GDP growth and the NPL ratio are shown to be the most reliable determinants of bank profitability. However, the estimated conditional distributions reveal that, while higher growth would raise profits on average, a large swath of banks would most likely continue to struggle even amid a strong economic recovery. Therefore, for some banks, a determined reduction in NPLs combined with cost efficiency improvements and customized changes to their business models appears to be the most promising strategy for durably raising profitability.